Clinical outcome of patients treated with spinal cord stimulation for therapeutically refractory angina pectoris. Issue 1 (1st July 1999) - TenVaarwerk, I A M; Jessurun, G A J; DeJongste, M J L; Andersen, C; Mannheimer, C; Eliasson, T; Tadema, W; Staal, M J
Abstract : OBJECTIVE: To determine morbidity and mortality characteristics in patients treated with electrical neuromodulation for refractory angina pectoris. DESIGN: A retrospective multicentre study of patients treated with spinal cord stimulation between 1987 and 1997; 21 centres were contacted and 14 responded. SETTING: Specialist centres worldwide. PATIENTS: Questionnaires were returned on 517 patients, of whom 71% were male. One was lost to follow up. Mean (SD) age was 63.9 (10.1) years. Duration of angina pectoris was 8.1 (6.3) years. RESULTS: Before spinal cord stimulation, 66% of the patients had experienced myocardial infarction, 68% had three vessel disease, and in 24% the left ventricular ejection fraction (LVEF) was ⩽ 40%. Percutaneous transluminal coronary angioplasty and bypass surgery were performed in 17% and 58% of the subjects, respectively. During a median follow up of 23 months (range 0 to 128), 103 patients died (52 from a cardiac cause, 25 from a non-cardiac cause, and 26 from an unknown cause). Annual all cause mortality was 7–8%; annual cardiovascular fatality was 3.5–5%. Mortality was univariately related to sex, number of diseased vessels, number of revascularisation procedures, previous myocardial infarction, LVEF, insulin dependent diabetes, β blocking agents, and angiotensin converting enzyme inhibitors. Multiple variate analysis showed that LVEF, sex, β blockers, and age ⩾ 71 years were independent predictors of mortality. During spinal cord stimulation, New York Heart Association functional class improved from 3.5 to 2.1 (p < 0.01); 25 of the deceased patients (24%) and 32 survivors (8%) experienced myocardial infarction; hospital admissions were significantly (p < 0.001) more common in the deceased group (66% v 37%). CONCLUSIONS: The clinical outcome of patients with intractable angina is not adversely affected by the chronic use of neurostimulation.